Upaya Peningkatan Pemulihan Tanaman Padi Terhadap Cekaman Terendam Melalui Perlakuan Pemupukan Setelah Terendam - Gribaldi Gribaldi; Rujito A. Suwignyo; Mery Hasmeda; Renih Hayati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
Plants get stressed shortly after submerged, to improve the recovery and subsequent metabolic processes as well as internal repairs required plant availability of adequate carbohydrate reserves after submerged. Giving fertilization treatment after being submerged is an effort to improve plant recovery after being submerged. This study was aimed to obtain the best fertilization to increase rice recovery to submergence stress through the fertilization after being submerged. The experimental design used was factorial completely randomized design with three replications. The factor consists of rice varieties (Inpara 3 dan IR 64) and treatment (N): Without soaking, basic fertilization (N1), submerged 7-14 DAP (fertilization of N, P2O5, K2O (N2), and fertilization of N, P2O5, K2O + (Si + Zn) (N3), as well as fertilization of N, P2O5, K2O + PPC micro (N4)) given 7 days after submerged, the submerged 7-14 and 28-35 DAP (N, P2O5, K2O (N5), and fertilization of N, P2O5, K2O + (Si + Zn) (N6) and fertilization of N, P2O5, K2O + PPC micro (N7)) given 7 days after the first submerged. The results showed that the growth and grain yield decreased with more frequent of rice plants in stress submerged condition. Fertilization can improve recovery after being submerged rice plants, where the best recovery obtained on varieties of rice plants treated with fertilization of N, P2O5 and K2O + PPC micro 7 days after being submerged.